Word frequencies and bigrams in bahasa Melayu - Don, Zuraidah Mohd.; Knowles, Gerry (Journal of Modern Languages, 2017)
This paper reports on some preliminary findings on word frequency in the MALEX database. The most frequent words are described, attention being paid to the position of content words in the frequency list. Nouns emerge as the most problematic to a particular set of genres, or even to a particular text. Bigrams are studied both as sequences of individual words and as sequences of grammatical tags. Whereas the tag sequences reflect syntactic rules and thus the hierarchical struture of syntax, sequence of individual words reflect quite a different kind of linear structure which has begun to emerge in recent years in corpus linguistcs.